Two new corticioid species of Phanerochaetaceae (Polyporales, Basidiomycota) from Southwest China - Zhang, Qiu-Yue; Liu, Zhan-Bo; Liu, Hong-Gao; Si, Jing (Frontiers in Cellular and Infection Microbiology, 2023)
Two new corticioid fungi in the family Phanerochaetaceae, Phanerochaete shenghuaii and Rhizochaete variegata, are described and illustrated from Southwest China based on morphological characteristics and molecular data. Phanerochaete shenghuaii is characterized by annual, effused, inseparable basidiocarps from substrate, ivory white to cream hymenial surface when juvenile, buff to yellowish brown with age, buff in KOH, a monomitic hyphal system, smooth cystidia, and ellipsoid basidiospores measuring 4.8–6 × 2.5–3.8 µm. Rhizochaete variegata is characterized by annual, effused, easily separable basidiocarps from substrate, buff-yellow to clay-pink fresh hymenial surface becoming cream to buff upon drying, violet in KOH, a monomitic hyphal system, encrusted cystidia, and ellipsoid basidiospores measuring 3–4 × 2.2–3 µm. The phylogenetic analyses based on ITS + nLSU rDNA sequences confirm the placement of the two new species, respectively, in the Phanerochaete clade and the Rhizochaete clade of Phanerochaetaceae. Phylogenetically related and morphologically similar species to these two new species are discussed.